Clinical predictors of sleep apnoea in heart failure outpatients. Issue 6 (18th February 2014) - Herrscher, T. E.; Akre, H.; Overland, B.; Sandvik, L.; Westheim, A. S.
Summary Background Sleep‐disordered breathing (SDB) is common in heart failure patients. Many of them still remain undiagnosed. The aim of this study was to detect clinical predictors of sleep apnoea which may help to identify patients with SDB at a heart failure clinic. Methods We performed an in‐home sleep study on 115 consecutive patients from our heart failure clinic. Clinical characteristics, blood samples, daytime sleepiness and quality of life were registered. Results Among 115 patients, 52% had moderate to severe SDB. Body Mass Index (BMI) ≥ 30 kg/m² was the only independent predictor of moderate to severe SDB [Odds ratio (OR) = 3.62, 95% Confidence interval (CI) 1.40–9.36, p = 0.008]. Quality of life and level of sleepiness were not significantly associated with SDB. Patients with mild to moderate chronic obstructive pulmonary disease (COPD) were unlikely to have SDB compared with patients without COPD (OR = 0.10, 95% CI 0.02–0.43, p = 0.002). Hypertension was a predictor of having obstructive sleep apnoea (OR = 2.78, 95% CI 1.15–6.75, p = 0.02), while haemoglobin ≥ 15 g/dl was associated with central sleep apnoea (OR = 6.71, 95% CI 1.96–22.99, p = 0.002). Conclusion BMI ≥ 30 kg/m2 is associated with moderate to severe SDB, both obstructive and central sleep apnoea. Thus, BMI may be used as one of the selection criteria for referral of heart failure patients to a sleep specialist.